Stomatal behavior of different grapevine cultivars in response to soil water status and air water vapor pressure deficit - Prieto, Jorge Alejandro; Lebon, Eric; Ojeda, Hernán (International Viticulture and Enology Society (IVES), 2021)
Aims: Genetic variability in grapevine cultivars may influence their strategy to cope with drought through stomatal regulation of transpiration rate. The aim of the present study was to evaluate the stomatal sensitivity of five cultivars (Ekigaïna, Grenache, Marselan, Mourvèdre, and Syrah) to soil water status and air water vapor pressure deficit (VPD). Methods and results: Leaf gas exchange and canopy light interception efficiency (εi) were evaluated through a wide range of predawn leaf water potential (ΨPD) measurements in a field experiment in Southern France. Additionally, greenhouse experiments were carried out to monitor stomatal response to increasing VPD levels. Ekigaïna showed a strong isohydric behavior with the highest decrease in leaf gas exchange in response to soil water stress and VPD. Mourvèdre and Grenache showed a similar but relatively less extreme behavior. These three cultivars showed a constant leaf water status during the day through stomatal regulation and a strong decrease in εi. In contrast, Syrah and Marselan displayed anisohydric behavior as they presented a less sensitive stomatal control. Both cultivars showed fluctuating midday leaf water potential and Marselan was the least affected in terms of εi. Conclusion: This study demonstrated that grape cultivars differed in their stomatal response to soil water deficit and VPD. For a given cultivar, a similar stomatal behavior was found in response to both ΨPD and VPD. Significance and impact of the results: Adaptation to drought and viticulture viability in hot and dry environments could be achieved by identifying and breeding cultivars with drought tolerance traits.